Enabling access to molecular monitoring for chronic myeloid leukemia patients is cost effective in China - Vikalp Kumar Maheshwari (Public Library of Science (PLoS), 2021)
Objective To determine the cost effectiveness of molecular monitoring in patients with chronic myeloid leukemia in the chronic phase (CML-CP) compared to no molecular monitoring from a Chinese payer perspective. Methods Analyses were conducted using a semi-Markov model with a 50-year time horizon. Population data from multicenter registry-based studies of Chinese patients with CML-CP informed the model. Transition probabilities were based on time-to-event data from the literature. Utility values were obtained from published studies and were assumed to be the same for patients with and without molecular monitoring. Costs were based on values commonly used in the Chinese healthcare system, including drug acquisition, drug administration, follow-up, treatment for disease progression, molecular monitoring, and terminal care costs, and were in the local currency (2020 Chinese Yuan RMB [¥]). Outcomes were total life-years (LYs) and quality-adjusted life years (QALYs), lifetime costs, and incremental cost-effectiveness ratio. Results Molecular monitoring was dominant to no molecular monitoring, with increased LYs (1.52) and QALYs (1.90) and costs savings (¥93,840) over a lifetime compared to no monitoring in discounted analyses. The opportunity of patients that receive molecular monitoring to discontinue treatment during treatment-free remission, an opportunity not afforded to those without molecular monitoring, was the principle driver of this result. Results were similar across multiple clinical scenarios. Particularly, molecular monitoring remained dominant even if the proportion of patients achieving deep molecular response (DMR) was reduced by 10%-30%, or the proportion of patients maintaining DMR for 1 year was reduced by 10%-30% or increased by 10%. Cost savings in these scenarios ranged from ¥62,230 to ¥103,964. Conclusions Overall, this analysis demonstrates that adherence to guideline recommendations of regular molecular monitoring of patients with CML-CP treated with TKIs provides significant clinical benefit that leads to substantial cost savings compared to no molecular monitoring from the perspective of a Chinese payer. In a time where healthcare systems have limited resources to allocate to optimal patient care, investment in molecular monitoring is an ideal choice for improving patient benefits at a reduced cost.